Real analysis : with proof strategies - Cunningham, Daniel W. (Boca Raton : Chapman & Hall, CRC Press, 2021)
"Typically, undergraduates see real analysis as one of the most difficult courses that a mathematics major is required to take. The main reason for this perception is twofold: Students must comprehend new abstract concepts and learn to deal with these concepts on a level of rigor and proof not previously encountered. A key challenge for an instructor of real analysis is to find a way to bridge the gap between a student's preparation and the mathematical skills that are required to be successful in such a course. Real Analysis: With Proof Strategies provides a resolution to the "bridging-the-gap problem." The book not only presents the fundamental theorems of real analysis, but also shows the reader how to compose and produce the proofs of these theorems. The detail, rigor, and proof strategies offered in this textbook will be appreciated by all readers. Features Explicitly shows the reader how to produce and compose the proofs of the basic theorems in real analysis Suitable for junior or senior undergraduates majoring in mathematics"--
OCLC-licensed vendor bibliographic record.
Keywords: Mathematical analysis -- Textbooks; Functions of real variables -- Textbooks; MATHEMATICS / Mathematical Analysis; MATHEMATICS / Calculus; MATHEMATICS / Functional Analysis